On optical solitons of the Schrödinger-Hirota equation with power law nonlinearity in optical fibers. (May 2017) - Aslan, Ebru Cavlak; Tchier, Fairouz; Inc, Mustafa
Abstract: In this study, we acquire optical soliton solutions of the Schrödinger-Hirota equation (SHE) in optical fiber. The integration algorithm employed in this work is the Jacobi elliptic function (JEF). We acquire new type JEF solutions, bright and dark optical solitons that are valuable in the field of optoelectronics. Constraint conditions are presented for the obtained solitons. The results show that this method is a powerful and efficient mathematical tool for solving problems in optical fibers. The remarkable features of such solitons are demonstrated by several interesting figures. Highlights: We use the Jacobi elliptic functions for the Schrödinger-Hirota equation with power law nonlinearity in optical fibers. We obtain new Jacobi elliptic function solutions, bright, dark optical solitons for this equation. We investigate the stability analysis for the obtained optical solitons. We get some interesting figures for the obtained solitons.